90 The protein expression of TNFR2 and STAT3 in high-grade serous ovarian cancer (HGSC) tissue and its association with platinum sensitivity. (13th November 2020) - Kampan, N; Silva Raju, J; Chew, K; Mohd Saleh, MF; Md Zin, RR; Jeganathan, R; Shafiee, MN; Abd Aziz, N
Abstract : Objective: To determine the relationship between TNFR2 and STAT3 in high-grade serous ovarian cancer (HGSC) tissues with chemotherapy response and prognosis outcome. Methods: This is a retrospective cohort study involving HGSC patients underwent primary cytoreduction followed by first-line adjuvant platinum-based chemotherapy with a minimum follow-up of 12 months. Tissue microarray slides were constructed utilising archived paraffin tissue from 25 chemo-naïve patients with HGSC and were stained for protein expression. Results: Overexpression of TNFR2 (48%) and STAT3 (60%) were found in the ovarian tissue of patients with advanced stage disease. The median PFS was significantly longer in the platinum sensitive (PS) compared to the platinum resistant (PR) group (18 vs 3 months, p=0.0001). In PS patients, median PFS is shown to be of longer trend in the weakly expressed compared to the overexpressed group among TNFR2 (31 vs 18 months, p=0.74) and STAT3 proteins markers (34 vs 18 months, p=0.693), but were not statistically significant. Unexpectedly, among the PR group, the TNFR2 overexpressed group showed significantly better PFS compared to TNFR2 weak group (90 vs 30 days, p=0.015). Conversely, among the PR group, the STAT3 overexpressed group showed significantly longer PFS compared to STAT3 weak expression group (120 vs 30 days, p=0.017). Conclusion: The PFS was found to be better trend among PS with TNFR2 or STAT3 weak expression tumour. Conversely, in the PR group, the PFS was longer among the strong protein expression tumour. Further study using a larger number of tissues is recommended to achieve statistical significance.